Conformational distortion in solution processable PVK:TcTa blends and the effect on extra warm white organic phosphorescent light emitting diodes - Woon, Kai Lin; Wong, Wah Seng; Chanlek, Narong; Nakajima, Hideki; Tunmee, Sarayut; Songsiriritthigul, C.; Lee, Vannajan Sanghiran; Songsiriritthigul, Prayoon (Elsevier, 2019)
Organic semiconductors generally display significant conformational flexibility which results in significant energetic disorder. In this research, ultraviolet photoelectron spectra are compared with the Gaussian density of states obtained from the density functional theory on assembly of molecules optimized using molecular dynamic simulations. It was found out that spin-coated organic semiconductor, tris(4-carbazoyl-9-ylphenyl)amine (TcTa), displays significant conformational distortion from its minimum geometry with significant Gaussian broadening. Adding poly(vinylcarbazole) (PVK) into TcTa results in increased face to face stacking of carbazole moieties from PVK as evident from increased red-shifted of absorption of PVK. Despite reduction of energy barrier upon addition of TcTa into PVK, the current efficiency of the extra warm white organic light emitting diodes showed limited improvement probably from the increased triplet quenchers from the carbazole dimers. © 2019